2022
DOI: 10.4097/kja.21330
|View full text |Cite
|
Sign up to set email alerts
|

Regional analgesia techniques for video-assisted thoracic surgery: a frequentist network meta-analysis

Abstract: This article has been accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination, and proofreading processes, which may lead to differences between this version and the version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…Following acceptance of the SRMA [ 6 ], a manuscript editor evaluating the proof found that one [ 5 ] of the included studies had been retracted for containing too many flaws to be corrected on September 9, 2021. The SRMA protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on April 29, 2021 (registration number: CRD42021252062), and a literature search was conducted in May 2021 on papers published between January 2000 and January 2021.…”
Section: What Happened During the Review Process?mentioning
confidence: 99%
See 1 more Smart Citation
“…Following acceptance of the SRMA [ 6 ], a manuscript editor evaluating the proof found that one [ 5 ] of the included studies had been retracted for containing too many flaws to be corrected on September 9, 2021. The SRMA protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on April 29, 2021 (registration number: CRD42021252062), and a literature search was conducted in May 2021 on papers published between January 2000 and January 2021.…”
Section: What Happened During the Review Process?mentioning
confidence: 99%
“…Given the ambiguous timing, several rounds of editorial discussions were necessary to thoroughly consider the options regarding how to proceed. The KJA editorial board made a concerted effort to perform peer review and editorial assessment in a robust, transparent, and credible manner regarding this disputed SRMA [ 6 ].…”
mentioning
confidence: 99%
“…The mechanism that mediates the coverage of the chest wall (other than back) of the ESP block appears to be due to the spreading of local anesthetics close to the paravertebral space where the dorsal and ventral rami of the spinal nerve diverge. Although there is a bunch of evidence showing the analgesic effect of ESP block in various types of surgery including breast, thoracic, and abdominal surgery, its use in cardiac surgery is still limited [35][36][37][38][39]. ESP block has some advantages in terms of safety and technical ease over thoracic paravertebral or epidural blocks which have risks such as hematoma, neural injury, or pneumothorax and are technically challenging.…”
Section: Erector Spinae Plane (Esp) Blockmentioning
confidence: 99%
“…5B). Although it has shown significant analgesic effects in thoracoscopic surgery, its analgesic effect seems smaller than that of paravertebral or ESP blocks [38]. Gautam et al [64], the only RCT that used SPB in cardiac surgery searched so far, evaluated the role of continuous deep-SAP block for postoperative pain relief in patients undergoing MIDCAB surgery via left anterior thoracotomy.…”
Section: Interpectoral Plane (Ipp) / Pectoserratus Plane (Psp) / Serr...mentioning
confidence: 99%
“…Since Hara et al. reported ultrasound-guided thoracic paravertebral nerve block (TPVB) in 2007 ( 8 ), it has been widely used in thoracic surgery such as in thoracoscopic lung surgery ( 9 ), breast surgery ( 10 ), rib surgery, and mediastinal surgery and thoracotomies. TPVB has a good analgesic effect in these surgeries.…”
Section: Introductionmentioning
confidence: 99%